Efeitos da Estimulação Transcraniana por Corrente Contínua (ETCC) sobre a fadiga muscular em corredores amadores - estudo clínico, crossover, controlado por sham, triplo-cego - Uehara, Laura Yukiko (2021)
The goal of this study is evaluate effects from tDCS in the fatigue applied before a quadríceps muscle fatigue protocol in recreational runners. Method: Twenty six recreational runners participated in this study, they were randomized to receive tDCS anodal(a) or sham(s) before fatigue protocol. Time of aplication 20 minutes, 2mA intensity, anode in the quadríceps femoral hotspot and cathode in the contralateral supraorbital area. Fatigue protocol in the quadríceps femoral has been done in the isokinetic dinamometer. The fatigue was evaluated by peak torque (N.m), fatigue resistance, cortical excitability (motor evocated potencial – MEP), lactate (mmol/l) and rate of perceived exertion (RPE). Results: Peak torque reduced from pre to pos intervention but there was not results intergroups in the peak torque (F=0.60, p <0.44; p2=0.18), fatigue resistance there was no difference between groups (p=0,97), lactate during fatigue protocol increased in the tDCSa (tDCSa 4,54(2,64−15,63) vs. tDCSs 3,91 (0,84−12,66)mmol/l; p=0,049), MEP reduced in both groups (tDCSa 246,52(0−613,75)mV vs 94,12[0−948,28]mV), (tDCSs 253,33[0−736,25]mV vs 94[0−563,63]mV), with no difference between groups (p=0,71) and RPE there was no difference between groups (tDCSa(8[4−10]) e tDCSs (7,5[4−10], p=0,56) Conclusion: It was observed that tDCSa single session in the cortical area before a fatigue protocol in the quadríceps femoral induced in lactate during fatigue protocol, but did not generate effects in peak torque, MEP, fatigue resistance and RPE.